The effectiveness of growth regulators and light color spectrum on callus growth of Amorphophallus muelleri Blume. var. Madiun1: Efektivitas zat pengatur tumbuh dan spektrum warna cahaya terhadap pertumbuhan kalus Amorphophallus muelleri Blume. var. Madiun1 - Wijaya, Agnes Natalia; Poernomo, Carlois; Savitri, Wina Dian; Irawati, Fenny; Hardjo, Popy Hartatie (Fakultas Pertanian Universitas Yudharta Pasuruan, 2023)
Introduction: Plant Growth Regulators (PGRs) play a role in regulating organogenesis and morphogenesis in shoots, roots, and callus formation. Color spectrum of light is one of the quality light factors that affects plant physiological processes. This study aimed to determine the effect of cytokinin and auxin on Murashige-Skoog (MS) medium and light on callus induction and proliferation of porang (Amorphophallus muelleri Blume.) var. Madiun1. Methods: This study used completely randomized design, with the first factor was PGRs (combination auxin and cytokinin) and the second was color spectrum of light (white light, blue light, and its combination) during incubation. Variables observed were emergence time, color, texture, structure and calli growth, also shoots emerging from calli. Results: The results showed an interaction between PGRs with a combination of light color spectrum on callus growth. The fastest callus growth occurred in combination 5.0 mg.l-1 6-benzyl amino purine (BAP) with 0.2 mg.l-1 naphthalene acetic acid (NAA) which was incubated in a combination of white and blue light for 16 hour irradiation. The combination 5.0 mg.l-1 BAP with 0.2 mg.l-1 NAA was able to induce callus emergence time, and the shoots appearing were faster, whereas combination of white and blue light was able to accelerate callus emergence from bulbil and adventitious shoots emergence. Conclusion: The combination of white and blue light color spectrum for 16 hours irradiation can accelerate callus emergence from bulbil and adventitious shoots emerging from calli, and interaction with combination of 5.0 mg.l-1 BAP and 0.2 mg.l-1 NAA can accelerate porang’s callus growth.